Materials engineering selection a product life cycle approach - Pfeifer, Michael (Butterworth-Heinemann, 2007)
There are books aplenty on materials selection criteria for engineering design. Most cover the physical and mechanical properties of specific materials, but few offer much in the way of total product design criteria. This innovative new text/reference will give the 'Big picture' view of how materials should be selected--not only for a desired function but also for their ultimate performance, durability, maintenance, replacement costs, and so on. Even such factors as how a material behaves when packaged, shipped, and stored will be taken into consideration. For without that knowledge, a design engineer is often in the dark as to how a particular material used in particular product or process is going to behave over time, how costly it will be, and, ultimately, how successful it will be at doing what is supposed to do